Clonación y expresión funcional de proteínas de la familia LCHR - León Márquez, Yhoana Laura (Universidad Michoacana de San Nicolás de Hidalgo, 2009)
The presence of high concentrations of chromate in the environment has led to the Selection of bacterial variants resistant to this ion. The determinant of resistance to Chromate most widely studied is the membrane protein ChrA. To date, Studied the ChrA proteins encoded in pseudomonas pUM505 plasmids Aeruginosa, Cupriavidus metallidurans pMOL28, Shewanella sp plasmid 1 and ChrA present in the TnOtChr transposon of Ochrobactrum tritici. ChrA is a protein Which expels chromate in a membrane-dependent manner. In A recent phylogenetic analysis identified 135 homologous ChrA sequences from the Three domains of life. These proteins were clustered in the superfamily of CHR transporters. CHR proteins were classified according to their size in LCHR proteins (345-495 aa) and in SCHR proteins (123-234 aa). LCHR proteins Bacterial infections were, in turn, grouped into six Subfamilies (LCHR1-LCHR6). The - The Burkholderia xenovorans and Burkholderia vietnamiensis proteobacteria are the Which have a higher number of genes encoding LCHR proteins; by way of Jointly present nine LCHR proteins from four distinct subfamilies. In addition to ChrAs mentioned, which are located in the subfamilies LCHR2 and LCHR5, there is no evidence That other members of the LCHR families confer chromate resistance, Objective of the present work is to determine if the LCHR proteins of B. xenovorans and B. Vietnamiensis confer resistance to chromate. One gene from each subfamily was chosen and Amplified by PCR, Were then cloned into a recovery vector for Subsequently subcloned into the vectors pUCP20 and pACYC184, high and low numbers Of copies, respectively.

La presencia de altas concentraciones de cromato en el ambiente ha dado lugar a la selección de variantes bacterianas resistentes a este ión. El determinante de resistencia a cromato más ampliamente estudiado es la proteína de membrana ChrA. A la fecha se han estudiado las proteínas ChrA codificadas en los plásmidos pUM505 de Pseudomonas aeruginosa, pMOL28 de Cupriavidus metallidurans, el plásmido 1 de Shewanella sp y la ChrA presente en el transposón TnOtChr de Ochrobactrum tritici. ChrA es una proteína hidrofóbica que expulsa cromato en forma dependiente del potencial de membrana. En un análisis filogenético reciente se identificaron 135 secuencias homólogas de ChrA de los tres dominios de la vida. Estas proteínas se agruparon en la superfamilia de transportadores CHR. Las proteínas CHR se clasificaron de acuerdo a su tamaño en proteínas LCHR (345–495 aa) y en proteínas SCHR (123–234 aa). Las proteínas LCHR bacterianas fueron, a su vez, agrupadas en seis subfamilias (LCHR1–LCHR6). Las - proteobacterias Burkholderia xenovorans y Burkholderia vietnamiensis son los organismos que presentan un mayor número de genes que codifican proteínas LCHR; de manera conjunta presentan nueve proteínas LCHR de cuatro subfamilias distintas. Además de las ChrAs mencionadas, que se ubican en las subfamilias LCHR2 y LCHR5, no existe evidencia de que otros miembros de las familias LCHR confieran resistencia a cromato, por lo que el objetivo del presente trabajo es determinar si las proteínas LCHR de B. xenovorans y B. vietnamiensis confieren resistencia a cromato. Se eligió un gen de cada subfamilia y se amplificaron por PCR, luego se clonaron en un vector de recuperación para posteriormente subclonarse en los vectores pUCP20 Y pACYC184, de alto y bajo número de copias, respectivamente.
Instituto de Investigaciones Químico Biológicas. Maestría en Ciencias en Biología Experimental
Keywords: info:eu-repo/classification/cti/6; IIQB-M-2009-0004; Clonación; Proteínas; LCHR; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3850